2017
DOI: 10.1186/s12967-017-1198-4
|View full text |Cite
|
Sign up to set email alerts
|

Experimental approach to IGF-1 therapy in CCl4-induced acute liver damage in healthy controls and mice with partial IGF-1 deficiency

Abstract: BackgroundCell necrosis, oxidative damage, and fibrogenesis are involved in cirrhosis development, a condition in which insulin-like growth factor 1 (IGF-1) levels are diminished. This study evaluates whether the exogenous administration of low doses of IGF-1 can induce hepatoprotection in acute carbon tetrachloride (CCl4)-induced liver damage compared to healthy controls (Wt Igf +/+). Additionally, the impact of IGF-1 deficiency on a damaged liver was investigated in mice with a partial deficit of this hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Using GFP-labeled mitochondrial proteins and transmission electron microscopy, we showed that mitochondrial mass and ultrastructural integrity were markedly protected in LPA-pretreated cells compared to the control cells without LPA pretreatment (Figure S4D). LPA-mediated hepatoprotective function was then tested using the established mouse model of CCl 4 -induced acute liver injury (Morales-Garza et al, 2017). The most effective in vivo PA concentration was determined based on tests in mice showing that intragastric gavage with 0.5 mg/mL of PA, but not 5.0 mg/mL or 100 mg/mL, increased mitochondrial Dcm and reduced O 2 À in the liver (Figure S5A).…”
Section: Lpa Reduces Mitochondrial Injury and Alleviates Hepatotoxicity Induced By CCLmentioning
confidence: 99%
“…Using GFP-labeled mitochondrial proteins and transmission electron microscopy, we showed that mitochondrial mass and ultrastructural integrity were markedly protected in LPA-pretreated cells compared to the control cells without LPA pretreatment (Figure S4D). LPA-mediated hepatoprotective function was then tested using the established mouse model of CCl 4 -induced acute liver injury (Morales-Garza et al, 2017). The most effective in vivo PA concentration was determined based on tests in mice showing that intragastric gavage with 0.5 mg/mL of PA, but not 5.0 mg/mL or 100 mg/mL, increased mitochondrial Dcm and reduced O 2 À in the liver (Figure S5A).…”
Section: Lpa Reduces Mitochondrial Injury and Alleviates Hepatotoxicity Induced By CCLmentioning
confidence: 99%
“…Interestingly, mice with a liver-specific IGF-1R knockout also displayed a strong impairment in hepatocyte proliferation and regeneration after partial hepatectomy [ 49 ]. Furthermore, a recent study by Morales-Garza et al demonstrated that IGF-1-deficient mice showed a reduced total liver weight on postnatal day 11, whereas subcutaneous IGF-1 administration attenuated this growth retardation, highlighting the important role of IGF-1 in liver growth [ 50 ]. However, these data are only in part comparable to our present experimental model, in which we expose the liver during fetal development and during the postnatal period to an adverse metabolic microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Existing experiments have also proved that IGF‐1 relieves the premature senescence of liver cells during liver injury (Luo et al, 2019). The liver Igf1 specific knockout experiment showed that the appropriate dose of IGF‐1 supplementation significantly protects the mouse livers during the ALI process and promote the regeneration of the mouse livers, and the level of IGF‐1 has a significant correlation with the level of liver damage (Mirpuri et al, 2002; Morales‐Garza et al, 2017). Our results confirm that knockdown of Mof in the liver stimulates liver cell proliferation by activating the IGF‐1 signaling pathway, reduces liver function damage caused by CCl 4 , and promote liver regeneration.…”
Section: Discussionmentioning
confidence: 99%